Tourism and hospitality management - Kozak, Metin, 1968-; Kozak, Nazmi (Bingley, U.K. : Emerald, 2016)
The book aims to address topics such as tourism education and its development in the latter part of the twentieth century, taking "tourism<U+201d> to be a broader field than "hospitality." The term "hospitality" refers to all operations or services encompassing accommodation and food/beverage facilities at the micro level, whereas "tourism" stands for the other elements at the macro level, including business, destination, and transportation operations. Moving from the generic to the specific, this book is divided into three main parts. Part I starts from a more generic perspective, and is entitled "Tourism Management." It comprises seven chapters by 13 scholars. Part 2 has a more moderate focus, and is entitled "Hospitality Management". It includes seven chapters contributed by 15 scholars from across the world. Part 3 is entitled "Education and Training in Tourism and Hospitality", and covers a range of topics from both tourism and hospitality. This last part consists of six chapters contributed by 13 scholars from four continents.
European quality award winning companies: a situational analysis / H. Kader S<U+0327>anlio<U+0308>z O<U+0308>zgen -- Service collaboration between healthcare service providers and tourism agencies / Elaine Y.T. Chew, Stephanie Onggo -- The transit tourists in Hong Kong / Priscilla Poon, Bob McKercher -- An actor network perspective of tourism open data / Maurice McNaughton, Michelle McLeod, Ian Boxill -- Marketing of tourism products through the Russian social media channel Vkontakte / Ekaterina Miettinen -- Key stakeholders in cruise traffic: an application to Spanish cruise ports / Jero<U+0301>nimo Esteve-Pe<U+0301>rez, Antonio Garci<U+0301>a-Sa<U+0301>nchez -- Revenue management: profit optimisation for Hong Kong travel agencies / Grace Chan, Basak Denizci Guillet -- Diffusion patterns in loyalty programs / Pedro Pimpa<U+0303>o, Anto<U+0301>nia Correia, Joa<U+0303>o Duque, Carlos Zorrinho -- Surprise, hospitality and customer delight in the context of hotel services / Ahmad Azmi Ariffin, Noor Omar -- Transferability of Asian paradigm in hospitality management to non-Asian countries / Athena Lele Chen, Kaye Chon -- The development of hospitality industry in Krakow: historical perspective / Robert Pawlusinski, Magdalena Kubal -- Diversification of hotels in a single-asset tourism city / Hilal Erkus-O<U+0308>ztu<U+0308>rk -- The branded content in the Balearic hotel chains / Angela Lemoine, Maria Garci<U+0301>a Sastre, Margarita Hormaeche -- Identification of organizational culture in the hospitality industry / Ali Bavik -- Developing intercultural skills for hospitality students in China / Alan Wong, Cathy Hsu -- Motivations of South Asian students to study tourism and hospitality in the UK / Roya Rahimi, Vipin Nadda, Blerton Hyseni, Dirisa Mulindwa -- Effect of work experience on students' attitudes towards hospitality careers / Marlena Bednarska, Marcin Olszewski -- The role of edu-tourism in bridging racial divides in South Africa / Julia Wells -- Higher education tourism courses in Brazil / Teresa Catramby, Priscilla Dutra -- Developing training programs for disabled guests: an industry perspective / Funda Cengiz.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Industries -- Hospitality, Travel & Tourism; Tourism industry; Tourism -- Management; Hospitality industry -- Management